Evolution of the financial sector: Three different stages: Repression, development and financialisation - Barradas, R. (Advances in applied business research: The L.A.B.S. Initiative, 2016)
This chapter makes a systematic literature review on the evolution of the financial sector in the last decades all over the world. This evolution was marked by three different stages, reflecting different impacts of the financial sector on the real economy and on society. The first stage – financial repression – is characterised by the existence of several regulations and restrictions on the financial sector, which proved to be detrimental to support economic growth. This legitimised the financial liberalisation and deregulation of the financial sector in the recent years in order to sustain the “finance-growth nexus” hypothesis, representing the second stage – financial development. Consequently, there was a strong growth of the financial sector in subsequent years, originating an excessive financial deepening and casting doubts around the advantages provided by the financial sector. In fact, excessive financial deepening weakened or reversed the relationship between savings and investments. These deleterious effects are commonly referred as financialisation, constituting the third stage. The chapter concludes that it is necessary to engage in a fourth stage in the coming years – definancialisation – in order to re-establish a more supportive relationship between the financial sector and economic growth and presents several policy recommendations around this matter.